Pengaruh Bahan Ajar dari Limbah Rumah Tangga Terhadap Kreativitas Peserta Didik pada Pembelajaran Seni Rupa Kelas V SDN Kutasari 02 Cipari (Indo-MathEdu Intellectuals Journal, 2025)
Learners who think creatively tend to understand a problem more easily and more quickly in solving problems. Learners' creativity can be developed through Fine Arts learning with diverse teaching materials, such as household waste. This study aims to find out whether or not there is an influence of teaching materials from household waste on students' creativity in Fine Arts learning class V at SDN Kutasari 02 Cipari. The research method used is quantitative research in the form of pre-experimental design. The researcher used a purpossive sampling technique where the sample taken was a class V student. The data was analyzed by one sample T test. The average score of the results of the students' creativity questionnaire after being treated was 82.06. The results of the One Sample T-test hypothesis test showed a significance value of 0.000. The significance value is less than 0.05 at the 95% confidence level, which means that Ho is rejected and Hα is accepted. So, it can be concluded that the use of teaching materials from household waste has an influence on the creativity of students in Fine Arts learning class V of SDN Kutasari 02 Cipari.